Penegakan Hukum bagi Pelaku Penipuan Tiket Konser Coldplay: Perspektif Hukum Pidana Islam - Muhammad Zaky; Dodi Irawan; Paisol Burlian (Journal of Sharia and Legal Science, 2025)
Concert ticket fraud cases often occur, especially for famous music concerts such as Coldplay concerts, which are a very famous music band in the world. As a result of the perpetrator's actions, many victims suffer losses, but the perpetrators only receive light sanctions. The purpose of this study is to analyze law enforcement against perpetrators of Coldplay concert ticket fraud from the perspective of Islamic criminal law. The type of research used is library research with secondary data sources. The primary legal material is the criminal code. The analysis was carried out descriptively qualitatively. The results of the study stated that law enforcement for perpetrators of Coldplay concert ticket fraud is based on Article 378 of the Criminal Code only, even though the act has also fulfilled the elements in Article 45 paragraph (2) Jo 28 Paragraph (1) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008, namely by utilizing technology as the object of his actions to spread news and mislead which makes someone interested so that it results in losses. While in Islamic criminal law, the crime of fraud is included in the category of Ta'zir crimes. In the decision of the panel of judges, it was implemented in accordance with the principle of ta'zir, only the sanctions given were still too light when compared to the consequences caused by the defendant.